Under the Background of "Internet +" Applied Undergraduate Research of Tourism Management Talents Training--Take Hainan Higher Vocational and Undergraduate Joint Training 4+0 Pilot as an Example. Issue 1 (February 2020) - Du, Changchun
Abstract: With the continuous progress of economic level, China's tourism in recent years has made rapid development. However, with the rapid development of tourism, a series of problems have emerged, among which the most significant one is the imbalance between tourism management talents and tourism development. The current tourism management personnel simply cannot adapt to the needs of the rapid development of tourism. In particular, the rapid development of the Internet has given birth to the "Internet + tourism" model and promoted the reform of the tourism industry. The rapid change of tourism industry means that tourism industry has entered a new period of development, but it also puts forward higher requirements. Tourism management talents are related to the development quality of tourism industry. Under the background of "Internet +", it has become an urgent problem to study the cultivation of application-oriented undergraduate tourism management professionals. Based on this, this article - to hainan vocational college and undergraduate cultivation 4 + 0 pilot project as an example, the first "Internet +" and "4 + 0" model for the relevant interpretation, on the basis of the information data algorithm and combined with the related experiment, analyzes the current status of tourism management talents cultivation, and puts forward some strategies on the cultivation of the tourism management specialized talented person.